Ambulatory Blood Pressure Monitoring Could Unmask Hypertension in Patients with Psoriasis Vulgaris - BACAKSIZ, AHMET; BACAKSIZ, AHMET; ONSUN, NAHIDE; Erdogan, Ercan; UYSAL, ÖMER; Sonmez, Osman; Sevgili, Emrah; Tasal, Abdurrahman; ONSUN, NAHİDE; Topukcu, Bugce; Kulac, Beytullah; UYSAL, ÖMER; et al. (My University, 2013)
Background: Psoriasis vulgaris is one of the most prevalent chronic, inflammatory skin disorders. Patients with psoriasis have excess risk of essential hypertension. Masked hypertension (MH), defined as normal office blood pressure (BP) with elevated ambulatory BP (ABPM), has been drawing attention recently due to its association with increased risk of developing sustained hypertension, cardiovascular morbidity, and mortality. The aim of this study was to investigate the prevalence of MH in psoriatic patients. Material and Methods: On hundred and ten middle-aged, normotensive, non-obese patients with psoriasis vulgaris and 110 age- and sex-matched normotensive controls were included in the study. ABPM was performed in all participants over a 24-h period. The clinical severity of the disease was determined according to current indexes. Results: The prevalence of MH among subjects with psoriasis vulgaris was 31.8% and increased compared to control subjects (p<0.01). Predictors of MH in patients with psoriasis vulgaris were detected as male sex, smoking, obesity-related anthropometric measures, and disease activity. Male sex, waist circumference, and diffuse psoriatic involvement were detected as independent predictors of MH. Conclusions: MH is prevalent in patients with psoriasis vulgaris. Assessment with ABPM and close follow-up for development of hypertension is reasonable.
Keywords: Hypertension